1989
DOI: 10.1002/ptr.2650030405
|View full text |Cite
|
Sign up to set email alerts
|

Schizontocidal activity of Celastrus paniculatus Willd. against Plasmodium falciparum in vitro

Abstract: Preparations from the plant Celartrus paniculatus Willd. have been used for treatment of malaria and other febrile illness in the traditional medicine practices of Thailand. Crude solvent extracts from the root bark and stem of C. paniculatus were screened for antimalarial activity against P . falcipamm using an in vitro culture system. A fraction of the chloroform extract of the root bark showed the bighest antimalarial activity. An active principle was isolated and characterized from the chbloroform fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…± Quinonemethide triterpenes are natural products of occurrence restricted to Hippocrateaceae and Celastraceae families. Several representatives of this class are claimed to be medicinally useful [1] [2], as antimicrobial [3 ± 5], anticancer [4] [6] [7], antimalarial [8], and spermicidal compounds [9]. Some Salacia species, e.g., S. reticulata, S. oblonga, and S. chinesis, have long been used in India, Sri-Lanka, and China, respectively, as traditional medicines for treating rheumatism and skin diseases, and for their anti-inflammatory properties as well.…”
mentioning
confidence: 99%
“…± Quinonemethide triterpenes are natural products of occurrence restricted to Hippocrateaceae and Celastraceae families. Several representatives of this class are claimed to be medicinally useful [1] [2], as antimicrobial [3 ± 5], anticancer [4] [6] [7], antimalarial [8], and spermicidal compounds [9]. Some Salacia species, e.g., S. reticulata, S. oblonga, and S. chinesis, have long been used in India, Sri-Lanka, and China, respectively, as traditional medicines for treating rheumatism and skin diseases, and for their anti-inflammatory properties as well.…”
mentioning
confidence: 99%
“…Many biological activities have been reported for members of this class of natural products, including antitumor,4,, 5 antileukemia,6 spermicides,6 antimalaria,7 and trypanomycides 8. Maitenin and pristimerin have been isolated from the Salacia species as potent antimicrobial agents 9…”
mentioning
confidence: 99%
“…Structure activity relationship studies on Triclisia alkaloids have shown that those with two ether bridges such as pycnamine are considerably more active than those with three ether bridges such as cocsuline (1.8), (lCso values 0.15 and 15.56 pg/mL, respectively) (Partridge et al, 1988). Tiliacorine (1.9), isolated from Tiliacora triandra has also been shown to have in vitro activity against Plasmodium falciparum (Pavanand et al, 1989b). The antimalarial mode of action of these alkaloids remains to be determined and so far no in vivo activity has been demonstrated.…”
Section: Isoquinoline Alkaloids Berberinementioning
confidence: 99%